2014
DOI: 10.4238/2014.february.21.15
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen peroxide enhances the uptake of polyethylenimine/oligonucleotides complexes in A549 cells by activating CaMKII independent of [Ca2+]c elevation

Abstract: ABSTRACT. Aerosol oligonucleotide therapy has vast potential in pulmonary system diseases. Reactive oxygen species (ROS) play an important role in complex physiological processes such as cell signaling, apoptosis, etc. Therefore, to determine the mechanism of ROS involvement in polyethylenimine/oligonucleotide (PEI /ON) 2914-2921 (2014) was almost completely abolished by the calcium/calmodulin-dependent protein kinase II (CaMKII) inhibitor and the microtube depolymerized drug. CaMKII-dependent microtube p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Considering the potential role of reactive species, hydrogen peroxide (H 2 O 2 ) was found to be capable of facilitating the endocytosis of polyethylenimine/oligonucleotide (PEI/ON) complexes, involving a cytoplasmic [Ca 2+ ]-independent activation of calcium/calmodulin-dependent protein kinase II (CaMKII), which stimulates cytoskeleton contractions and transportation 39 . It was also found that the ROS generated in mitochondria mediate the hypoxia-induced endocytosis in alveolar epithelial cells 40 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the potential role of reactive species, hydrogen peroxide (H 2 O 2 ) was found to be capable of facilitating the endocytosis of polyethylenimine/oligonucleotide (PEI/ON) complexes, involving a cytoplasmic [Ca 2+ ]-independent activation of calcium/calmodulin-dependent protein kinase II (CaMKII), which stimulates cytoskeleton contractions and transportation 39 . It was also found that the ROS generated in mitochondria mediate the hypoxia-induced endocytosis in alveolar epithelial cells 40 .…”
Section: Discussionmentioning
confidence: 99%
“…It is considered that the endocyosis of cells can be stimulated by CAP via reactive species and other mechanisms such as membrane damage, as indicated above 39 , 42 , 43 . In gene transfection, the clathrin-dependent endocytosis stimulated by CAP was found to be dominant in the uptake, while synergistically combining with electrical effects 43 .…”
Section: Discussionmentioning
confidence: 99%
“…They also describe that H 2 O 2 increases polyethylenimine/oligonucleotide endocytosis by activating the calcium/calmodulin-dependent protein kinase II (CaMKII). This study suggests that H 2 O 2 may be useful to improving aerosol oligonucleotide therapy in pulmonary diseases [ 18 ]. Zhang et al also observed that H 2 O 2 increases the cytoplasmic Ca 2+ concentration in A549 cells [ 19 ]; this change in calcium concentration might be a critical regulator of apoptosis.…”
Section: Effects Of H 2 O 2 mentioning
confidence: 99%